Subclinical Hypoventilation in Dogs Undergoing Ventral Slot Decompressive Surgery for Cervical Myelopathy Due to Intervertebral Disc Herniation - Andruzzi, Melissa N.; Simon, Bradley T.; Boudreau, Elizabeth (Frontiers in Veterinary Science, 2021)
The objective of this prospective cohort study was to document the occurrence of postoperative hypoventilation in dogs undergoing decompressive ventral slot or hemilaminectomy for the treatment of intervertebral disc herniation (IVDH). 20 dogs undergoing ventral slot surgery and 20 dogs undergoing hemilaminectomy surgery for the treatment of IVDH that presented to XX between 2017 and 2020 were enrolled. Dogs were anesthetized using a standard protocol. Blood gas samples were taken at up to 11 time points beginning during anesthetic recovery and continuing for a maximum of 72 hours postoperatively. Dogs with cervical lesions that were non-ambulatory before surgery had more evidence of subclinical hypoventilation in the immediate peri-extubation period than dogs with less severe injuries or those undergoing hemilaminectomy surgery. We found no difference in the ventilation status in dogs undergoing cervical or thoracolumbar decompressive surgery for IVDH from eight to 72 hours postoperatively. Other markers of acid-base status indicated that subclinical hypoventilation within the peri-extubation period was transient and self-limiting. There was a moderate positive correlation between sedation scores and estimated PaCO2. These data suggest that dogs with severe cervical spinal cord injuries may be at risk for subclinical hypoventilation in the immediate peri-extubation period. Increased sedation may be correlated with decreased ventilatory status in dogs recovering from decompressive vertebral column surgery.